Risk factors for postdischarge growth retardation among very-low-birth-weight infants: A nationwide registry study in Taiwan - Wei-Li Liao; Ming-Chih Lin; Teh-Ming Wang; Chao-Huei Chen (Elsevier, 2019)
Background: Very-low-birth-weight (VLBW) infants have a high risk of postdischarge growth retardation (GR). Continued GR might exert negative long-term effects on their health. This study examined the prevalence and the risk factors for postdischarge GR among VLBW infants in Taiwan. Methods: Nationwide data from the Taiwan Premature Infant Follow-up Network between 2007 and 2011 were analyzed. Infants with a gestational age (GA) < 37 weeks and birth body weight (BBW) < 1500 g were enrolled. They were followed up after discharge at the corrected ages of 6, 12, and 24 months. Associations between postdischarge GR at the follow-ups and possible risk factors were analyzed. Results: The prevalence of postdischarge GR among 2124 VLBW infants was 17.3%, 19.4%, and 13.8% at the corrected age (CA) of 6, 12, and 24 months, respectively. The significant perinatal factors of postdischarge GR were being small for gestational age (SGA) and extremely low birth weight (ELBW). ELBW infant with extra-uterine growth retardation (EUGR) at discharge or longer length of hospital stay (LOS) had poorer growth outcomes. Among non-ELBW infants, EUGR at discharge and surgical necrotizing enterocolitis (NEC) were the main influencing factors of unfavorable growth outcomes. RDS with surfactant therapy had a positive effect of postdischarge growth outcomes in ELBW infants. Conclusion: Postdischarge GR is still a serious problem in Taiwan. Being SGA and ELBW and EUGR were significant risk factors for postdischarge GR throughout the first two years of life in VLBW infants. An integrated and organized team for postdischarge care as well as scheduled follow-ups, detailed nutritional education, and thorough inspection are necessary. Key Words: growth disorders, infant, premature, risk factors, very low birth weight